Design strategies and application of stimuli-responsive nanoparticles for cancer diagnosis and therapy - Marasini, Ramesh (Kansas State University, 2020)
Small molecule anticancer drugs are the first-line therapy used in clinical cancer management which has shown success in the killing of rapidly dividing cancer cells. However, nonspecific distribution of these small molecular therapeutics has adverse side effects reducing the quality of life. Therefore, in the past few decades, massive interest and investment have been given in cancer nanomedicine with the hope to reduce drug-associated toxicity by targeting cancer cells in a heterogeneous tumor environment. Nanomedicine is the drug-containing nanostructured construct with a large surface-to-volume ratio, which has plenty of room to load drugs and other necessary constituents to design it as target-specific. Towards the endeavor of precise anticancer drug delivery to tumors, significant efforts have been given to obtain an optimized nanocarrier system to co-operate or bypass biological barriers further advancing the therapeutic and diagnostic efficiency of drugs. The main objective of this dissertation is to explore the different strategies of nanomaterials for drug delivery via light-triggered and magnet sensitive design considerations discussed in chapter 1. The synthesized nanomaterials were extensively studied and evaluated for their chemistry and biological functions for in vitro cancer therapy and in vivo diagnosis. In chapter 2, we developed the optimum surfactant packing strategy for light-responsive gold nanoparticles (NPs) for photothermal therapy (PTT) of melanoma. Results showed that 5 kDa polyethylene glycol (PEG) coated gold nanorod provided the highest colloidal stability and maximum photothermal efficiency compared to the low (2 kDa) and high mass of PEG (10 kDa) used when treated with near-infrared (NIR) laser. Taking one step further, in chapter 3, we encapsulated NIR light-responsive indocyanine class of dye (IR-820) into polymeric NPs for the PTT of breast cancer. The optical properties of dye were preserved to obtain better photothermal efficiency than free IR-820 at an equivalent concentration of dye after laser treatment. Moreover, the molecular mechanism of PTT revealed that the dye loaded NPs inducedcell death primarily through apoptosis, a preferred cell-death pathway over necrosis. In chapter 4, we designed peptide conjugated lipid-polymer NPs for p32 targeted drug delivery and tracked NIR dye-labeled NPs in vivo using an optical imaging system. The targeted NPs were accumulated 2-fold higher than non-targeted counterparts in the murine osteosarcoma model suggesting the diagnostic potential of targeted NPs. In chapter 5, we developed magnet responsive iron chelated paramagnetic polymeric NPs with high colloidal stability and longitudinal relaxivity of 10.5 mM⁻¹s⁻¹ as compared to the Magnevist® 3.98 mM⁻¹s⁻¹ (a clinical gadolinium contrast agent) and enhanced contrast efficacy in vivo at clinical magnetic resonance imaging (3 T) system showing its promise as a blood pool contrast agent in disease detection. The nanoconstructs described herein addresses the current limitations of conventional nanoparticles via different design considerations. The significant findings such as targeted drug delivery with improved therapeutic and diagnostic efficacy of each system are highlighted and discussed throughout the dissertation. These results could open the avenues for systemic investigations and lay the foundation for the design of cancer nanomedicine to accelerate clinical translation.
Keywords: Nanomedicine; Photothermal Therapy; Magnetic Resonance Imaging; Fluorescence Imaging; Cancer theranostics; Iron-based T1 contrast agent